ChemInform Abstract: Strongly Exchange Coupled Core|Shell Nanoparticles with High Magnetic Anisotropy: A Strategy Toward Rare‐Earth‐Free Permanent Magnets. Issue 36 (August 2016) - Lottini, E.; Lopez‐Ortega, A.; Bertoni, G.; Turner, S.; Meledina, M.; Van Tendeloo, G.; de Julian Fernandez, C.; Sangregorio, C.
Abstract: Antiferromagnetic(AFM)/ferrimagnetic(FiM) Co0.3 Fe0.7 O/Co0.6 Fe2.4 O4 core‐shell nanoparticles (NPs) with a particle size of 6—18 nm are prepared by a one‐pot thermal decomposition process according to the literature involving mixed Fe and Co oleate complexes.